2004
DOI: 10.5089/9781451851199.001
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Shocks, Learning, and Open Economy Dynamics

Abstract: This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. I study the implications of productivity shocks in a model where agents observe the aggregate level of productivity but not its permanent and transitory components separately. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Interestingly though, while the coeffi cient of Cluster 1 with low expected value of the shocks is found to be small, those of Clusters 2 and 3 with high expected values are large. This fi nding indicates that the coeffi cient gets larger for the countries subject to large productivity shocks, a result that is in line with the simulation studies by Mendoza (1997) and Miniane (2004). This implies that it is the magnitude rather than the variability of shocks that matters.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly though, while the coeffi cient of Cluster 1 with low expected value of the shocks is found to be small, those of Clusters 2 and 3 with high expected values are large. This fi nding indicates that the coeffi cient gets larger for the countries subject to large productivity shocks, a result that is in line with the simulation studies by Mendoza (1997) and Miniane (2004). This implies that it is the magnitude rather than the variability of shocks that matters.…”
supporting
confidence: 76%
“…Thus, they do not predict that saving responds to a permanent but not persistent shock. However, Miniane (2004) has demonstrated that a permanent shock that is not persistent can also generate a positive saving reaction thanks to the learning process. A learning agent might view part of the permanent shock as temporary due to imperfect information and hence initial response of saving to a permanent shock might be positive.…”
Section:  Prague Economic Papers 3 2009mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, Cardia [9] demonstrated that the failure of real interest rate equalization can lead to a high association between S-I. Secondly, the studies [21,4,19] showed that exogenous disturbances, such as productivity or technology shocks, might result in a co-movement of S-I. For instance, with positive productivity shocks, households get wealthier which give rise to both higher consumption and saving under the assumption that consumption has a smoothing behavior.…”
Section: Introductionmentioning
confidence: 97%
“…Rather, the government knows only the relative variances of the two shocks. It thus faces a "signal extraction" problem similar to one originally proposed by Muth (1960) (see also Harvey, 1989, andMiniane, 2004).…”
mentioning
confidence: 99%